Callogenesis and Somatic embryogenesis induction in Hevea brasiliensis: effects of fruit shelf-life and carbon source - Modeste, Kouassi Kan; Edmond, Koffi Kouablan; Gilles, Konkon N’dri; Michel, Gnagne; Mongomaké, Koné; Hilaire, Kouakou Tanoh (Research in Biotechnology, 2012)
An experiment was conducted to study the effect of the fruit shelf-life and the concentrations of carbon source on somatic embryogenesis via callogenesis of Hevea brasiliensis. Fruits harvested were stored at 15Ã‚Â°C during 1, 5, 7, 12 and 15 days and the inner integuments obtained from seed were used as explants. The experiments were performed under carbon source treatments with three concentrations for glucose and five concentrations for sucrose. Under these conditions, the percentage ofÃ‚Â explants forming calli was better during the first week of fruitÃ‚Â preservation regardless of the carbon source but at high concentration. However, beyond 7 days of fruits shelf-life, sucrose is best to induce callus unlike glucose but with high concentration. The best rate of embryogenic calli was also obtained with sucrose. The percentages of callogenic explants and embryogenic calli have decreased sharply with the shelf-life of fruit at 15Ã‚Â°C. So, to maintain an embryogenic potential of explants in situations of long-term conservation of fruits, sucrose can be used at 234 mM of concentration or default at 111 mM sucrose. These sucrose concentrations are conducive to induce embryogenic calli withÃ‚Â explants coming to rubber fruits after a long time of preservation.